MAKNA KONOTATIF DALAM PIDATO DONALD JOHN TRUMP - Runtuwene, Verell Rievaldo Junio; Pamantung, Rina P.; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research entitled â€œMakna Konotatif dalam Pidato Donald John Trumpâ€. This research examines about connotative meaning found in Donald John Trumpâ€™s speech. This study has two research problems, which are the kinds of lingual forms that have connotative meanings described on Donald Trumpâ€™s speech and the functions of connotative meanings stated on Donald Trumpâ€™s speech. The aim of this research is to identify and classify the kind of lingual forms and analyze and describe, the functions of connotative meaning on Donald John Trumpâ€™s speech. The data were taken from several Donald John Trumpâ€™s speech such as Donald Trump Inauguration Speech on 21st January, 2021, Donald Trumpâ€™s speeches to United Nation General Assembly, President Donald Trump delivers annual address at State of the Union 2020 and Donald Trump Farewell speech from White House. The researcher uses a semantic theory by Geoffrey Leech (1981). The researcher identified and classified the phrases and sentences and then analyzed and described the connotative meaning. As the result, there are 40 phrases which consist of connotative meaning. The researcher found also there are 14 phrases with informational function, 13 phrases with expressive function, 10 phrases with aesthetic function, 2 phrases with phatic function and 1 phrase with directive function that found in this research.Keywords: Connotative Meaning, Semantic Analysis, Donald John Trumpâ€™s Speeches